Reconstructing Peace Fines for Economic Crimes: Prosecutorial Discretion, Restorative and Transformative Justice within an Islamic Legal Ethics Framework - Sutrisno Margi Utomo; M. Arfin Hamid; Amir Ilyas; Ali Rahman (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
The enforcement of economic criminal law in Indonesia confronts a persistent tension between procedural efficiency and substantive justice. This article examines the reconstruction of peace fines as an alternative resolution mechanism for economic crime cases within the Attorney General’s authority as dominus litis. Employing normative legal research with statutory and conceptual approaches, the study argues that peace fines reflect prosecutorial discretion consistent with restorative justice objectives, particularly the recovery of state losses and the restoration of social balance. Nevertheless, current implementation remains fragmented and vulnerable to legal uncertainty, unequal outcomes, and governance risks due to unclear standards, institutional capacity gaps, and weak accountability architecture. The analysis is structured around four issues: (1) the doctrinal position of the prosecution service as dominus litis; (2) the philosophical justification of peace fines using Radbruch’s triad of justice, utility, and legal certainty; (3) an institutional and systemic reading informed by Friedman’s legal system framework; and (4) a transformative-justice reconstruction model emphasizing proportionality, transparent criteria, and layered accountability. Crucially, this article situates the reconstruction of peace fines within the framework of Islamic legal ethics, arguing that the principles of maqasid al-shariʻah — particularly hifz al-mal (protection of property/wealth) and ʻadl (justice) — provide a normative foundation that is compatible with, and enriches, the transformative justice model proposed. The convergence of Islamic legal thought and modern restorative justice mechanisms offers a contextualized approach to economic crime resolution that is especially relevant in a Muslim-majority society such as Indonesia. The proposed model aims to align peace fines with fair, consistent, and auditable law enforcement outcomes.